Evaluation of water demand scenarios for the Olifants River catchment, South Africa - McCartney, Matthew P.; Arranz, Roberto (2009)
Water resource development has played a key role in the expansion of agriculture, mining and industry in the Olifants River catchment, but the colonial and apartheid regimes have left a legacy of inequity. Currently water deficit is one of the major constraints hampering further development and demand for water continues to grow. Against this background, the Water Evaluation And Planning model was used to provide a preliminary assessment of both the current situation and three plausible future scenarios. For each scenario the model was used to simulate water-use in five sectors (i.e., rural, urban, mining, irrigation and commercial forestry) over a 70-year period of varying rainfall and flow. Levels of assured supply were estimated and the economic cost of failing to supply water was predicted. Current shortfalls are estimated to be costing between US$ 6 and 50 million per year, depending on rainfall and, hence, river flows. If increases in demand are not checked this will increase significantly. Under a high demand scenario, the economic benefits increase greatly but, even with infrastructure development and improvements in demand management, the economic cost of insufficient water supply rises to US$ 10.5 million in most years and, in exceptionally dry years, up to US$ 312 million.